2006
DOI: 10.1128/jcm.00057-06
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Naturally Occurring Humoral and Cellular Mutated Epitopes of Hepatitis B Virus in a Chronically Infected Argentine Patient with Anti-HBs Antibodies

Abstract: Serum hepatitis B virus (HBV)DNA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…The first region contains both a major histocompatibility complex class I (MHC-I)-restricted T-cell epitope and a B-cell epitope, while the second region, at least up to aa 207, displays both MHC-II T helper epitopes and B-cell epitopes. It was also reported that changes within this second region, located immediately downstream of the a determinant, may cause alterations in the structural component of such immunogenic determinant [30,34].…”
Section: Hbsag Mutantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first region contains both a major histocompatibility complex class I (MHC-I)-restricted T-cell epitope and a B-cell epitope, while the second region, at least up to aa 207, displays both MHC-II T helper epitopes and B-cell epitopes. It was also reported that changes within this second region, located immediately downstream of the a determinant, may cause alterations in the structural component of such immunogenic determinant [30,34].…”
Section: Hbsag Mutantsmentioning
confidence: 99%
“…Thus, antibodies targeting this determinant are supposed to protect against re-infection with any of the HBV genotypes [29]. Changes in the conformation which can successively alter the binding of neutralizing antibodies can occur due to amino acid substitutions within the a determinant [30].…”
Section: Hbsagmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in the conformation which can successively lead to failure of binding of neutralizing antibodies may develop due to amino acid substitutions within the" a" determinant [30]. Mutations in HBV occur due to low fidelity of polymerase, high replication rate and overlapping reading frames.…”
Section: Hepatitis B Surface Antigen (Hbsag)mentioning
confidence: 99%